(untitled) (Research, Society and Development, 2021)
Information Technology, based on its results and usage needs, has a timely and relevant scenario in the current context. It becomes fundamental in companies’ strategies, exploring opportunities and generating competitive advantages at all levels of management. Its impacts are notorious at the internal and external levels of organizations: on the organic structure and the role of framing / coordination in the organization; the psycho-sociological level and personal relationships; in the subsystem of objectives and values ​​of the people who work in the organizations; as well as in the technological subsystem. In this context, the study aimed to emphasize the framework (structure) practiced and its importance in the context of competitive advantages in organizations. To meet the growing demand for innovation, creativity, quality, process improvement, competitiveness among many other needs in this globalized world. As a methodological design, the article is characterized as a bibliographic, exploratory, documentary, descriptive, explanatory and qualitative research. It is inferred that the window of advantage (the period of time it takes competitors to reach and match the strategic advantage) has become a critical issue in terms of management. The challenge is to find the managerial connections between IT, the proposed and necessary information technology solutions, which meet the business needs, and the business objectives.